PENGARUH PROFESIONALISME KERJA TICKETING STAFF TERHADAP LAYANAN TAMU PADA TRAVEL FAIRMON MANADO - Merry Adrah; Agus Walansendow; Rahmawati Tohari (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2023)
The tourism industry is one of the largest sources of foreign exchange in several countries. Many countries have been working on tourism seriously for the last few years and have made tourism a leading sector, both in terms of earning foreign exchange, creating jobs, and alleviating poverty. There is no doubt about the important role of tourism in economic development in various countries. Fairmon Tours and Travel Manado took part in the tourism industry competition which was established in 1995 which was originally called Maya Express Tours & Travel with experience in operating the travel industry, in providing services to consumers. Moreover, it is supported by the strategic location of travel because initially it was in the Bahu Mall Block W1 Shopping Complex, then moved to Jl. Lembong no. 3-5 which is the center of Manado city. It is expected that they will always maintain service quality standards for guests and all existing employees are equipped with work professionalism and working skills that guests feel that their needs are met by using Fairmon travel Manado services. Ticketing department employees, including ticketing staff, carry out their duties and responsibilities to serve all guest needs, be it for ticket pick-up or tour packages, so that guests are satisfied as a form of work professionalism. The technique used in this research is a quantitative method while the data are collected by observation, interviews, documents and questionnaires. The method used is analysis with simple linear regression where variable X is Work Professionalism and variable Y is Guest service with the equation Y = a+b. The final result after calculating a simple linear regression analysis is the equation Y = 26.5 + 0.27 indicates that each increase of one variable unit (X) Work Professionalism will cause a change in variable increase (Y) Guest service of 0.27 and vice versa, the determinant coefficient r2 = 0.29383 or 29.38%. This shows that the guest service variable caused by work professionalism is 29.38%, the remaining 70.62% is influenced by other factors such as lack of knowledge, discipline, courtesy and creativity in serving guests. For this reason, it is hoped that Fairmon Tours & Travel will maintain and improve work professionalism so that the number of guest visits increases.